A RADIOCARBON DATING APPROACH TO THE DEPOSITION AND REMOVAL OF HUMAN BONE REMAINS IN MEGALITHIC MONUMENTS. Issue 5 (27th October 2020) - Aranda Jiménez, Gonzalo; Díaz-Zorita Bonilla, Marta; Hamilton, Derek; Milesi, Lara; Sánchez Romero, Margarita
ABSTRACT: The formation of commingled human bone assemblages is a key aspect for better understanding funerary rituals. The megalithic cemetery of Panoría (Spain) provides an excellent opportunity to explore bone assemblage formation thanks to the recent excavation of an undisturbed burial. For this purpose, we have approached the differential skeletal representation found between bone and teeth at the site through radiocarbon ( 14 C) dating and Bayesian modeling. The comparison between the series of 14 C dates on bone (n=12) and teeth (n=14) stress three main aspects: (1) the dates of teeth show a long period of funerary use before the deposition of the human bone remains; (2) both kinds of samples appear to be chronologically sequenced; the end of the teeth 14 C series matches with the beginning of human bone deposition; and (3) bone remains span a short period, not more than a few decades, which probably represents the last episode of intense mortuary activity. These differences suggest that teeth could be the evidence of skeletal depositions subsequently removed from the tomb. The deposition and removal of bone remains emerge as key aspects in the formation of the bone assemblage.